2014
DOI: 10.1155/2014/454701
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume in Patients with Obstructive Sleep Apnea and Its Relationship with Simpler Heart Rate Derivatives

Abstract: Some studies show increased mean platelet volume (MPV) in obstructive sleep apnea (OSA). The aim of this study was to evaluate MPV in OSA patients without cardiovascular risk factors and the possible association of heart rate derivatives with MPV. A total of 82 patients (aged 30–70 years) were divided into 2 groups according to the presence of either OSA or non-OSA as the control group. The OSA group consisted of 52 patients and the control group consisted of 30 subjects. Neither group was significantly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Other indices including MPV and plateletcrit were not different then the control. As mentioned above, there are several studies reporting no difference in MPV between patients with OSA and control (13)(14)(15)(16)(17)(18). The studies reporting difference in MPV, found that MPV was higher only in patients with severe OSA (but not milt-moderate OSA) than the control group (4)(5)(6)(7)9).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Other indices including MPV and plateletcrit were not different then the control. As mentioned above, there are several studies reporting no difference in MPV between patients with OSA and control (13)(14)(15)(16)(17)(18). The studies reporting difference in MPV, found that MPV was higher only in patients with severe OSA (but not milt-moderate OSA) than the control group (4)(5)(6)(7)9).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover in some studies, it was proposed that treatment with continuous positive airway pressure (CPAP) devices and surgical intervention significantly reduce MPV and PDW values in patients with severe OSA (10)(11)(12)24). On contrary, almost similar number of study reported no relationship between MPV and OSA, and between PDW and OSA (13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Red cell and platelets indices have been extensively investigated in various diseases. Limited, controversial information is available, however, on the association between red cell [15][16][17][18][19] and platelets [15,[20][21][22][23][24][25] parameters and the severity of OSAS. Therefore, the aim of this study was to investigate the levels of these parameters in patients with OSAS and to assess whether there is any correlation between the severity of OSAS and any of these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…These covariates included demographic, psychological (eg, depression), chronic diseases (eg, diabetes), behavioral (eg, physical activity), and cardiovascular biomarkers (eg, mean platelet volume, white blood cells), all known to associate with sleep. Covariates included age (years; continuous), 14 gender, 14 race–ethnicity (Mexican American, non-Hispanic white, non-Hispanic black, and other), 14 measured body mass index (kg/m2; continuous), 15 education (<ninth grade, 9-11, high school, some college, college or more), 14 cotinine (ng/mL; continuous), 16 white blood cells (1000 cells/μL; continuous), 17 iron (μg/dL; continuous), 18 physician diagnosis of diabetes (yes/no), 19 physician diagnosis of coronary artery disease (yes/no), 20 measured mean arterial pressure (mm Hg; continuous), 20 self-report engagement in moderate-to-vigorous physical activity in the past 30 days (yes/no), 21 mean platelet volume (fL; continuous), 22 red blood cell distribution width (%; continuous), 13 and Patient Health Questionnaire-9 (PHQ-9) determined moderate or greater (PHQ-9 score ≥10) depression symptomology. 23 Details on the assessment of these covariates are reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%